Patient Satisfaction Is Viewed From The Dimension Of Empathy In Health Services In The Emergency Room At Morowali Hospital - ito, Wulan Permatasari; Nur Wijayanti; Joko Prasetyo (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2024)
Hospital RSUD Morowali is a governmant issued hospital morowali built since the 2003 budget year through dana DHS-ADB, APBN and APBD with lots of land 5 Ha and the spacious building 5.155,48 m2. The existence of regional task force (SKPD) RSUD Morowali in accordance with the regents rule Morowali Number :188.3/0930/RSUD/2008 October 17, 2008 RSUD Morowali it’s been working since 2006 and has received permission from central Sulawesi provincial health services Number :445/04.68/DINKES l 27 Februari 2008.The purpose of this study is to explore patients satisfaction from the dimension of empathy in emergency room health services as well as the focus of the research being lift. 1) exploring in putting the patients interests at stake RSUD Morowali. 2) tours of duty officers were friendly in emergency installations RSUD Morowali 3) exploring officers served with manners on RSUD Morowali 4) Counter discriminate reconnaissance of service officers 5) scanning officers serve and appreciate every patients in the er RSUD morowali. The study uses qualitative research methods of sapling observation interview deep and documentation and then the data is analysed by the presentation of data and the conclution examination. Results from the research obtained where the emergency room workers were on RSUD morowali in giving health care promptly no problem and appropriate SOP In emergency installations and in general services the officers provided no problem but there were some patien who experienced discomfort to the officers who seems to have poor manners which gives the patient a poor impression. In this case, it is expected that emergency room workers will be more hospitable and have very high empathy.